The Effectiveness of Early Science and Mathematics Development E-Modules to Improve Early Childhood Concept Understanding - Khotimah, Nurul; Pamuji; Astawan, I Gede (Mimbar Ilmu, 2024)
In today's digital era, learning that used to only be carried out face-to-face is increasingly shifting to hybrid. Where all universities implement online and offline learning. This study aims to evaluate the effectiveness of using e-modules in early science and mathematics development to improve conceptual understanding in early childhood. E-modules designed interactively and based on multimedia are used as teaching aids for children aged 4-6 years. The research method used is a quasi-experimental with a pre-test and post-test design in two groups, namely the experimental group using e-modules and the control group using conventional learning methods. The results showed that children in the experimental group experienced a significant increase in conceptual understanding compared to the control group, with an average increase in mathematical concept understanding. In addition, e-modules have also been shown to increase children's interest in learning and active involvement in the learning process. Obstacles faced during the study included limited access to technology and the need for training for teachers to optimally utilize e-modules. In conclusion, e-modules for early science and mathematics development are effective in improving conceptual understanding in early childhood, as long as they are supported by adequate infrastructure and good teacher competence in operating them.